2004
DOI: 10.1371/journal.pbio.0020328
|View full text |Cite
|
Sign up to set email alerts
|

The Program of Gene Transcription for a Single Differentiating Cell Type during Sporulation in Bacillus subtilis

Abstract: Asymmetric division during sporulation by Bacillus subtilis generates a mother cell that undergoes a 5-h program of differentiation. The program is governed by a hierarchical cascade consisting of the transcription factors: σE, σK, GerE, GerR, and SpoIIID. The program consists of the activation and repression of 383 genes. The σE factor turns on 262 genes, including those for GerR and SpoIIID. These DNA-binding proteins downregulate almost half of the genes in the σE regulon. In addition, SpoIIID turns on ten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
434
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(467 citation statements)
references
References 106 publications
23
434
1
2
Order By: Relevance
“…42 Feed-forward loops of this type are widespread regulatory elements and are implicated in sign-sensitive delay and preventing inactivation of the target gene program when input signals are lost (i.e., they serve as stabilizers of target gene expression) and have been shown to be relevant in the context of cellular differentiation. [42][43][44][45] Our analysis of Grhl2-deficient mice revealed that Grhl2 is required for nephric duct lumen expansion in vivo. Because globally Grhl2-deficient mice exhibit embryonic lethality at E11.5, 8 we were unable to analyze the role of Grhl2 in the ureteric bud or the collecting duct of the developing and mature kidney in this model.…”
Section: Discussionmentioning
confidence: 79%
“…42 Feed-forward loops of this type are widespread regulatory elements and are implicated in sign-sensitive delay and preventing inactivation of the target gene program when input signals are lost (i.e., they serve as stabilizers of target gene expression) and have been shown to be relevant in the context of cellular differentiation. [42][43][44][45] Our analysis of Grhl2-deficient mice revealed that Grhl2 is required for nephric duct lumen expansion in vivo. Because globally Grhl2-deficient mice exhibit embryonic lethality at E11.5, 8 we were unable to analyze the role of Grhl2 in the ureteric bud or the collecting duct of the developing and mature kidney in this model.…”
Section: Discussionmentioning
confidence: 79%
“…This is another example of a cell cycle control circuit design feature that enhances robustness by preventing timing glitches (2). The regulatory configuration of CtrA and SciP and their coregulated genes fits the type-1 incoherent feedforward loop circuit motif that is found in many regulatory circuits, often in arrangements in which multiple functionally related genes are coordinately regulated (21)(22)(23). The type-1 incoherent feedforward loop motif is a regulatory configuration in which an activator (i.e., CtrA) controls a target gene (e.g., a flagellar gene) and also activates a repressor of that target gene (i.e., SciP).…”
Section: Discussionmentioning
confidence: 93%
“…The Spo0F protein has been identified in both Bacillus subtilis and B. anthracis as being involved in one of the early/intermediate phosphor-relay events that leads to sporulation (27) (Fig. 3), and mutants in spo0F have been generated that do not sporulate because of lack of signal (28,29).…”
Section: Discussionmentioning
confidence: 99%